2021
DOI: 10.1038/s41467-021-27047-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Gluconobacter oxydans knockout collection for improved extraction of rare earth elements

Abstract: Bioleaching of rare earth elements (REEs), using microorganisms such as Gluconobacter oxydans, offers a sustainable alternative to environmentally harmful thermochemical extraction, but is currently not very efficient. Here, we generate a whole-genome knockout collection of single-gene transposon disruption mutants for G. oxydans B58, to identify genes affecting the efficacy of REE bioleaching. We find 304 genes whose disruption alters the production of acidic biolixiviant. Disruption of genes underlying synth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Schmitz et al. recently built a whole-genome map of acid production by G. oxydans ( Schmitz et al., 2021 ), the first step in whole genome engineering. Added together these breakthroughs make something that appeared almost impossible a few years ago, appear tantalizingly possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Schmitz et al. recently built a whole-genome map of acid production by G. oxydans ( Schmitz et al., 2021 ), the first step in whole genome engineering. Added together these breakthroughs make something that appeared almost impossible a few years ago, appear tantalizingly possible.…”
Section: Discussionmentioning
confidence: 99%
“…Rowe et al, 2018 discovered that S. oneidensis can use imported electrons to reduce NADH, and characterized the genes behind this pathway (Rowe et al, 2021). Schmitz et al recently built a wholegenome map of acid production by G. oxydans (Schmitz et al, 2021), the first step in whole genome engineering. Added together these breakthroughs make something that appeared almost impossible a few years ago, appear tantalizingly possible.…”
Section: Ll Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A deeper understanding of Fe/S-oxidizing microbes’ genes is nonetheless still needed for more detailed metabolic engineering towards desirable biomining properties, compared to the model chassis Escherichia coli and Saccharomyces cerevisiae . Schmitz et al (2021) harnessed high-throughput genome editing and sequencing approaches in the study of heterotrophic bacterium Gluconobacter oxydans to produce organic acids for rare earth elements biomining. They created a library of single-gene transposon mutants in G. oxydans and found the bioleaching rates of rare earth elements increased up to 18% when phosphate-specific transport systems genes were disrupted.…”
Section: Advances Of Synthetic Biology-enhanced Biominingmentioning
confidence: 99%
“…2,5-DKG is commonly and directly synthesized using D-glucose as a substrate. In addition to 2,5-DKG being the precursor of 2-KLG, recent studies reported its synthesis may also increase rare-earth element recovery in wastewater (Jindra et al, 2016;Schmitz et al, 2021). As 2,5-DKG reactions during synthesis and decomposition processes are unclear, further research in these areas may provide insights on one-step 2-KLG synthesis and environmental protection.…”
Section: Introductionmentioning
confidence: 99%